Transgenically encoded protein photoinactivation (FlAsH-FALI): acute inactivation of synaptotagmin I. - Marek, K.W.; Davis, G.W. (Neuron, 2002)
We demonstrate a noninvasive technique for protein photoinactivation using a transgenically encoded tag. A tetracysteine motif that binds the membrane-permeable fluorescein derivative 4',5'-bis(1,3,2-dithioarsolan-2-yl)fluorescein (FlAsH) was engineered into synaptotagmin I (Syt I4C). Neuronally expressed Syt I4C rescues the syt I null mutation, can be visualized after FlAsH labeling, and is normally distributed at the Drosophila neuromuscular synapse. Illumination of FlAsH bound Syt I4C at 488 nm decreases evoked release in seconds demonstrating efficient fluorophore-assisted light inactivation (FlAsH-FALI) of Syt I. The inactivation of Syt I is proportional to the duration of illumination and follows first-order kinetics. In addition, Syt I FlAsH-FALI is specific and does not impair Syt I-independent vesicle fusion. We demonstrate that Syt I is required for a post-docking step during vesicle fusion but does not function to stabilize the docked vesicle state.